MENINGKATKAN KEMAMPUAN SISWA DALAM MEMBACA PUISI DENGAN METODE DEMONTRASI SISWA KELAS V SEKOLAH DASAR - Rahmani Rahmani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This research aims to increase students ability in reading poetry with demonstration methods in class V SDNegeri 005 Koto Perambahan Kecamatan Kampa Kabupaten Kampar. The subject of this research is thestudents class V with the number of students 28. The research was conducted two cycles. Each cycle is doneseveral stages is action planning, action implementation, observation and evaluation, and reflection. The resultsof research showed that in cycle I total of complete students is 8 students or 28.6% with low category. In thecycle II the number of completed students increased to 25 students or 89.2% in the medium category. Based onthe result of the research, it can be concluded that the use of demontration methods can improve students abilityin reading poetry students of class V SD Negeri 005 Koto Perambahan.